2015
DOI: 10.1007/s13224-015-0698-5
|View full text |Cite
|
Sign up to set email alerts
|

Pros and Cons of Adding of Neoadjuvant Chemotherapy to Standard Concurrent Chemoradiotherapy in Cervical Cancer: A Regional Cancer Center Experience

Abstract: Background The present study summarizes the results of treatment in the form of disease-free survival and overall survival in bulky stage IB2 and locally advanced (stages II-IVA) squamous cell carcinoma of the uterine cervix. The treatment has been given in the form of NACT followed by CCRT in one arm and CCRT in the other arm. The grade 3/4 hematologic toxicities were more in the NACT group than CCRT (p \ 0.001) while the non-hematological toxicity was not significant; the TPF group experienced more toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
0
14
1
1
Order By: Relevance
“…In the present study, NACT did not bring advantages in OS and PFS. Harsh et al [17] showed that the 3- and 5-year OS and disease-free survival (DFS) in 332 patients who received NACT combined with concurrent chemoradiotherapy were significantly longer than in those who received concurrent chemoradiotherapy alone, as supported by Marita et al [18] Narayan et al [19] analyzed 612 patients with locally advanced cervical carcinoma, and compared NACT combined with concurrent chemoradiotherapy vs chemotherapy alone, and similar results were obtained. For these patients, it is possible that giving NACT and then performing sequential concurrent chemoradiotherapy may achieve better clinical outcomes.…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, NACT did not bring advantages in OS and PFS. Harsh et al [17] showed that the 3- and 5-year OS and disease-free survival (DFS) in 332 patients who received NACT combined with concurrent chemoradiotherapy were significantly longer than in those who received concurrent chemoradiotherapy alone, as supported by Marita et al [18] Narayan et al [19] analyzed 612 patients with locally advanced cervical carcinoma, and compared NACT combined with concurrent chemoradiotherapy vs chemotherapy alone, and similar results were obtained. For these patients, it is possible that giving NACT and then performing sequential concurrent chemoradiotherapy may achieve better clinical outcomes.…”
Section: Discussionmentioning
confidence: 80%
“…Cervical cancer represents the third leading cause of cancer death in females in the developing countries 2. India accounts for nearly one-third of cervical cancer deaths worldwide, with ~132,000 new cases and 74,000 deaths reported each year 3. The current screening methods to detect cervical cancer include cytological-based Pap smears and human papillomavirus (HPV) lesions detected through HPV testing 4.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence supporting the use of NACT prior to RT/CCRT is limited, with most data comprising retrospective case studies from India [19][20][21], or small phase II trials [5,[22][23][24] that often had short follow up periods and reported response rate rather than survival. Until very recently, there was no randomised evidence available.…”
Section: Results In the Context Of Published Literaturementioning
confidence: 99%